Interactions between symptoms and psychological status in irritable bowel syndrome: An exploratory study of the impact of a probiotic combination. Issue 1 (30th September 2022) - Groeger, David; Murphy, Eileen F.; Tan, Hern Tze Tina; Larsen, Ida Søgaard; O'Neill, Ian; Quigley, Eamonn M. M.
Abstract: Background: Stress is an exacerbator of irritable bowel syndrome (IBS) symptoms, and anxiety and depression are co‐morbidities. Bifidobacterium longum strains 1714® and 35642® attenuate stress responses in healthy people and reduce symptoms in IBS, respectively. Here, we explore relationships between the psychological and visceral effects of the two strains (COMBO) in IBS subjects and biomarkers of stress and inflammation. Methods: We recruited 40 patients with IBS (Rome III) and mild to moderate anxiety (HADS‐A) and/or depression (HADS‐D) and 57 asymptomatic female controls with low or moderate stress. IBS patients were fed COMBO (1 × 10 9 cfu/day) for 8 weeks with an 8‐week washout. IBS symptoms, psychometric measures, salivary cortisol awakening response (CAR), and plasma inflammatory biomarkers were assessed every 4 weeks. Key results: Compared to healthy controls, IBS subjects had a blunted CAR. Treatment with COMBO restored CAR and improved IBS symptoms compared to baseline during the treatment phase. The COMBO reduced HADS‐D, HADS‐A score, and TNF‐α, while sleep quality improved significantly from baseline to the end of the intervention. Surprisingly, these parameters improved further once treatment ended and maintained this improvement by Week 16. Conclusions and inferences: These findings suggest that the stress response is a major driver of IBS symptoms. The time course of the beneficial effect of COMBO on IBS symptoms suggests that this is achieved through a restoration of the stress response. In contrast, the time course of the effects of COMBO on anxiety and depression in IBS paralleled an anti‐inflammatory effect as indicated by a reduction in circulating levels of TNF‐α. Abstract : The probiotic combination restored the blunted cortisol response associated with IBS which was mirrored by clinically significant improvements in overall IBS symptoms, but the effect lasted only for the duration of treatment. The probiotic combination reduced depression, anxiety scores, and circulating levels of TNFα, as well as improving sleep quality.